Ureditev dostopa do Vrhovnega sodišča z vidika odvetnika - Testen, Matija (Podjetje in delo, 2015)
The amendments to the Slovenian Civil Procedure Act (ZPP-D) introduced some major changes. The mindset of parties (including attorneys) which still comprehend the Supreme Court as the third court instance, the instance which will provide a rightful decision, i.e. a decision in their favor in a concrete case, however, remained unchanged. The article focuses on reasonableness of duality of access to the Supreme Court, as well as maintaining the value of the civil claim as a criterion for the allowed appeal on points of law from the viewpoint of Supreme Court's role under the Constitution. By highlighting the concrete real-world cases, this article exposes the unnecessary formal requirements, as well as the interpretation and use of these requirements by the Supreme Court which is often too strict. The consequence of maintaining the value of a civil claim as a criterion for allowed appeal on points of law in combination with often too strict interpretation of formal requirements leads to the conclusion that the Supreme Court may hear the cases, which from the legal point of view are not objectively relevant, while some cases involving important legal questions are rejected due to strict formal requirements.
Keywords: odvetniki; pristojnosti; revizija; sodišča; sodne odločbe; vrhovna sodišča